Cultores da Terra Sagrada missão e tradução nas Serras da Ibiapaba (Céculo XVII) - Maia, Lígio José de Oliveira (2005)
This paper analyzes how changes involving Jesuit indicators and - and, to a lesser extent, other colonial agents - were made in the contacts in the Ibiapaba Mountains during the 17th century in the flagship of Seara Grande.[...]